2011
DOI: 10.1371/journal.pgen.1002033
|View full text |Cite
|
Sign up to set email alerts
|

Genome-Wide Meta-Analysis Identifies Regions on 7p21 (AHR) and 15q24 (CYP1A2) As Determinants of Habitual Caffeine Consumption

Abstract: We report the first genome-wide association study of habitual caffeine intake. We included 47,341 individuals of European descent based on five population-based studies within the United States. In a meta-analysis adjusted for age, sex, smoking, and eigenvectors of population variation, two loci achieved genome-wide significance: 7p21 (P = 2.4×10−19), near AHR, and 15q24 (P = 5.2×10−14), between CYP1A1 and CYP1A2. Both the AHR and CYP1A2 genes are biologically plausible candidates as CYP1A2 metabolizes caffein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
202
0
8

Year Published

2011
2011
2021
2021

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 198 publications
(221 citation statements)
references
References 35 publications
(45 reference statements)
11
202
0
8
Order By: Relevance
“…It is not clear if either alcohol or caffeine is indeed responsible for the protective feature or if there is a genetic setup that makes individuals be alcohol or coffee lowers and at the same time protects them form diabetes. Very recently, Cornelis et al (60) reported the a genome-wide association study of habitual caffeine intake on large number (>47,000) individuals within the United States. They found two loci: 7p21 (P=2.4x10 -19 ), near AHR, and 15q24 (P=5.2x10 -14 ), between CYP1A1 and CYP1A2 associated with high daily caffeine intake.…”
Section: Risk Of Diabetes and Life Stylementioning
confidence: 99%
“…It is not clear if either alcohol or caffeine is indeed responsible for the protective feature or if there is a genetic setup that makes individuals be alcohol or coffee lowers and at the same time protects them form diabetes. Very recently, Cornelis et al (60) reported the a genome-wide association study of habitual caffeine intake on large number (>47,000) individuals within the United States. They found two loci: 7p21 (P=2.4x10 -19 ), near AHR, and 15q24 (P=5.2x10 -14 ), between CYP1A1 and CYP1A2 associated with high daily caffeine intake.…”
Section: Risk Of Diabetes and Life Stylementioning
confidence: 99%
“…Genome-wide association studies have identified several genetic loci associated with caffeine/coffee consumption (26)(27)(28)(29). We extracted results for these SNPs from our genomewide G-E interaction analysis to better illustrate their potential functions.…”
Section: Resultsmentioning
confidence: 99%
“…Some previous studies have examined the relationship between caffeine metabolism and genetics [83][84][85][86][87][88][89][90]. Most of them examined the relationship between coffee consumption and gene polymorphism of the caffeine receptor (A2A) or liver enzymes (cytochrome P450).…”
Section: Discussionmentioning
confidence: 99%